Efficiency of Indonesian Zakat Institutions in Times of Covid-19: A Two-Stage DEA Analysis - Prakoso, Muhammad Fajar Dito; Kurnia, Ariel Izza; Ikhwan, Ihsanul (Center of Strategic Studies (PUSKAS) BAZNAS, 2023)
This study evaluates the efficiency level of Selected Amil Zakat Institutions (OPZ) in Indonesia with a span of 2017–2021. Data Envelopment Analysis and Tobit Regression were employed to evaluate OPZ performances. The findings show that only two out of 14 OPZ in Indonesia have experienced perfect efficiency, i.e., LAGZIS Peduli in 2017 and LAZISNU in 2019-2021. The inefficiency that befalls OPZ in Indonesia mostly comes from the output variable, i.e., the collection and distribution of social funds. It is expected that OPZ in Indonesia can optimize the collection and distribution of social funds. Another unique finding is that the OPZ in Indonesia tends to stabilize its efficiency level during the COVID-19 pandemic, namely in 2020 and 2021. The Tobit regression shows that the factors of institution size and number of branch offices have a significant influence on the efficiency level of OPZ in Indonesia, inversely proportional to the factors of age and affiliation of Amil Zakat Institutions, which have no significant effect on the efficiency level of the institution